Desarrollo de un plugin para implementación de audio espacial en proyectos musicales y audiovisuales (2018)
The implementation of spatialization and sound field rotation methods, is being widely used in the development of musical and audiovisual content. The developers of this type of technology allow the users to spatialize or recreate an audio file in a room by means of convolution with impulse responses given by the providers, limiting the users to have the possibility to recreate a specific room of interest with determinate acoustics characteristics. In consequence, it is proposed the development of a tool that allows the user to do both things, to spatialize such as to recreate an audio file in a room, giving him the freedom to load any impulse response. This tool consist in a .VST plugin that spatializes by means HRTFs. The process of spatialization also contemplates the loss of level by distance and the real-time convolution with an impulse response with the objective of locate an audio file in the tri-dimensional space recreated in a specific room. It also allows to control the input and output level of the signal, the azimuth and elevation angles and the influence of the impulse response. The development of this tool was done in the programming language cSound in the development environment Cabbage. As result of this research, it was obtained a .VST plugin with graphical user interface that allows the control and automation of its parameters